A T‐cell diagnostic test for cystic echinococcosis based on Antigen B peptides. (24th November 2017) - Petrone, L.; Vanini, V.; Amicosante, M.; Corpolongo, A.; Gomez Morales, M. A.; Ludovisi, A.; Ippolito, G.; Pozio, E.; Teggi, A.; Goletti, D.
Summary: Cystic echinococcosis (CE) immunodiagnosis is still imperfect. We recently set‐up a whole‐blood test based on the interleukin (IL)‐4 response to the native Antigen B (AgB) of Echinococcus granulosus . However, AgB is encoded by a multigene family coding for five putative subunits. Therefore, the aims of this study were to analyse the IL‐4 response to peptides spanning the immunodominant regions of the five AgB subunits and to evaluate the accuracy of this assay for CE diagnosis. Peptides corresponding to each subunit were combined into five pools. A pool containing all peptides was also used (total pool). IL‐4 evaluated by enzyme‐linked immunosorbent assay was significantly higher in patients with CE compared to those without (NO‐CE subjects) when whole‐blood was stimulated with AgB1 and with the total pool. Moreover, IL‐4 levels in response to the total pool were significantly increased in patients with active cysts. Receiver Operator Curve analysis identified a cut‐off point of 0.59 pg/mL predicting active cysts diagnosis with 71% sensitivity and 82% specificity in serology‐positive CE patients. These data, if confirmed in a larger cohort, offer the opportunity to develop new diagnostic tools for CE based on a standardized source of AgB as the peptides.